Construction Law From Beginner to Practitioner - Mason, Jim (James Robert) (2016)
This innovative book provides a thorough and comprehensive guide to construction law by blending together black letter law and socio-legal approaches. This mixed methodology makes an ideal introduction to the subject for those studying to enter the Architecture, Engineering and Construction (AEC) Industry in a professional capacity.
Includes bibliographical references and index.
Keywords: Construction industry -- Law and legislation -- Great Britain; Construction contracts -- Great Britain; Law